Analisis Pengaruh Komunikasi Terbuka, Kepemimpinan Empati Dan Pelatihan Lintas Generasi Y Terhadap Kinerja Organisasi Swasta - Jaenab Jaenab (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
. This study aims to analyse the effect of open communication, empathetic leadership, and cross-generational training for Generation Y on the performance of private organisations. This research employs a quantitative approach with an associative design. The population consists of all Generation Y employees working in private organisations, with a sample of 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analysed using multiple linear regression. The results show that: (1) partially, open communication has no significant effect on private organisational performance; (2) partially, empathetic leadership has no significant effect on organisational performance; (3) cross-generational training for Generation Y has a positive and significant effect on organisational performance; and (4) simultaneously, the three variables have a positive and significant effect on private organisational performance with a contribution of 50.2 per cent. These findings indicate that improvements in private organisational performance are driven primarily by training programmes that are responsive to the characteristics of Generation Y, so organisations need to ensure that open communication and empathetic leadership are translated into concrete development practices.